Domestic cooked cheese - Slavko Kirin (Mljekarstvo)
The research results of sensory properties, chemical and microbiological quality of domestic cooked cheese, which is produced around Bjelovar region, are presented in this paper.Domestic cooked cheese is Croatian autochthonous cheese produced in wider north-western region of Croatia (Bilogora, Lika, Banovina, Gorski Kotar and around Zagreb), and therefore should be registered as Protected Denomination of Origin (PDO) and/or Protected Geographical Indication (PGI). Sensory properties, chemical and microbiological analyses were performed on 16 samples (7 non-smoked and 9 smoked cheeses). All cheese samples were produced according to tradition. Significant unevenness was determined in sensory, chemical and microbiological quality. Domestic cooked cheese can be classified as soft cheese according to dry matter content, and as semi-hard cheese according to water content in non fat cheese matter. According to fat content in dry matter, domestic cooked cheese can be classified as fat cheese. Standardization elements are proposed.